2002
DOI: 10.1016/s0014-5793(02)02672-8
|View full text |Cite
|
Sign up to set email alerts
|

Most immunoglobulin heavy chain switch mu rearrangements in B‐cell chronic lymphocytic leukemia are internal deletions

Abstract: We investigated 38 cases of B-cell chronic lymphocytic leukemia (B-CLL) for the presence of non-productive rearrangements in the SW W regions and defined for the first time the molecular nature of these rearrangements. Southern blot analysis revealed SW W region rearrangements in 13 cases (34%) and polymerase chain reactions (PCRs) indicated that these rearrangements consisted of internal deletions of the SW W region. Long-distance PCRs localized the SW W deletions in the V H DJ H rearranged allele in most cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…40 In particular, this seeming contradiction has been described multiple times in B-cell malignancies such as Burkitt lymphoma and CLL as well as in extracerebral and central nervous system diffuse large B-cell lymphoma. 41,42 In MALT lymphoma, switch recombination is often "illegitimate," that is, involving only 1 rather than 2 switch sites and leading to an aberrant rearrangement of the IgH switch region not actually accompanied by isotope switching. 42 The fact that the IgV H genes of both our panels of murine and human tumor antibodies are somatically hypermutated and, at least in approximately 50% of cases, are subject to ongoing mutation suggests that antigen plays a role during the initiation and the progression of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…40 In particular, this seeming contradiction has been described multiple times in B-cell malignancies such as Burkitt lymphoma and CLL as well as in extracerebral and central nervous system diffuse large B-cell lymphoma. 41,42 In MALT lymphoma, switch recombination is often "illegitimate," that is, involving only 1 rather than 2 switch sites and leading to an aberrant rearrangement of the IgH switch region not actually accompanied by isotope switching. 42 The fact that the IgV H genes of both our panels of murine and human tumor antibodies are somatically hypermutated and, at least in approximately 50% of cases, are subject to ongoing mutation suggests that antigen plays a role during the initiation and the progression of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…We used a second green-labeled probe that was centromeric to the IGH locus to identify the chromosomes. 13 These probes were co-hybridized to cell metaphases from 33 tumors for which cytogenetic materials were available (Figure 4b, Supplementary Figures 1-4 Large internal deletions within the Sm region occur exclusively in IgM þ DLBCLs and cluster on the productive IGH loci…”
Section: Vh Gene Mutation Analysismentioning
confidence: 99%
“…Thus, this observation raises the possibility that some element necessary for isotype switching may have been inactivated on this allele. Remarkably, large deletions within the Sm region, which have been proposed to participate in the stabilization of IgM in several other mature B-cell malignancies, [13][14][15] have also been shown to occur frequently in ABC DLBCLs. 6 To test the hypothesis that these deletions may play a role during the Isotype class switching in DLBCL P Ruminy et al development of this disease, we searched for shortened Sm regions in our series by genomic PCR (Figure 5a).…”
Section: Vh Gene Mutation Analysismentioning
confidence: 99%
“…A similar hypothesis has been proposed for the role of DSl in 'IgM-isotype stabilization' in normal mouse B cells (Zhang et al, 1995). Internal Sl deletions, which are closely related to physiological CSR, are restricted to germinal center or post-germinal center B-cell derived malignancies like BL, follicular lymphoma, B-cell chronic lymphocytic leukemia (Nardini et al, 2002), and hairy cell leukemia (own unpublished observations), and are not found in lymphomas derived from pregerminal center B cells such as mantle cell lymphoma (data not shown). In this study, we show that not all BL cases with downstream switch breakpoints have a DSl, and opposite not all BL cases with DSl show downstream switch breakpoints.…”
Section: Internal Sl Deletions Burkitt Lymphomas and Cell Linesmentioning
confidence: 94%
“…Integrity of Sl was assessed by LD-PCR using three overlapping primer sets, which span from the intronic enhancer (El) to the coding region of Cl. The Sl region was amplified using the 5M1-3M primer set (Fenton et al, 2003), whenever this yielded a band of the expected size (germline Sl); genomic DNA was subsequently subjected to LD-PCR with the 5 0 rl-3MRB primer set, located 5 0 from the 5M1-3M primer set, and the 5MFB-CmR1 primer set (Nardini et al, 2002), located 3 0 from the 5M1-3M primer set. Sequences of primers are listed in Table 2.…”
Section: Long-distance Pcrmentioning
confidence: 99%